Description of Posner Schlossman Syndrome Patients in Bandung, Indonesia during the Period of August 2009 to July 2011 - Arunasalam, Kavitha; Tjahjaningtyas, Erna; Ekowati, RA.Retno (Althea Medical Journal, 2015)
Â Â Â Background: Posner-Schlossman Syndrome (PSS) is also known as Glaucomatocyclitic Crisis. It is a nonâgenetic, often misdiagnosed, and rare disease characterized by recurrent unilateral episodes of markedly elevated intraocular pressure which occurs simultaneously with mild inflammation of the uvea. The underlying cause of this disease is still unknown. This syndrome usually affects those who are 20 to 50 years old. The aim of this study was to perform a descriptive study on subjects diagnosed with PSS at the National Eye Centre Cicendo Eye Hospital Bandung Indonesia.Â Methods: The method used was a descriptive study carried out on subjects diagnosed with PSS at the National Eye Centre Cicendo Eye Hospital Bandung, Indonesia during the period of August 2009 to July 2011.Results: Of 31 patients, 19 (61.3%) female patients participated in the study, 12 (38.7%) aged 31â40 years, 9 (29.0%) had recurrences. All (100%) complained of blurred vision, 24 (77.4%) with accompanying vision of rainbow halo surrounding light in, and 22 (71%) had headache. A total of 27 (87.1%) patients suffered from the disease unilaterally. After treatment, 17 (54.8%) patientsâ visual acuity improved and 20 (64.4%) patientsâ intraocular pressure (IOP) were in normal range.Â Conclusions: PSS mostly affects females. The most prevalent age range is 31â40 years. Most are affected unilaterally. All of them present with the symptom ofÂ blurred vision. Visual acuity and IOP are in normal limit after treatment.Keywords:Â Eye vision, Posner Schlossman Syndrome, National Eye Centre Cicendo Eye HospitalDOI: 10.15850/amj.v2n1.421Â